Studi Kasus: Analisis Permasalahan Bimbingan dan Konseling yang sering Dialami Siswa di SMPN 22 Medan - Akhir Pardamean Harahap; Muhammad Syahbagus; Hidayatul Fikri Koto (Departement of Mathematics Education, 2023)
Counseling is an important activity in an education that originates directly in human life. Students who do not carry out their obligations as natives who carry out the mandate as the nation's generation also need good handling. As well as the lack of awareness of discipline in students. Especially in terms of guidance counseling which is based on religion. This study aims to describe the Analysis of Guidance and Counseling Problems that are Often Experienced by Students at SMP N 22 Medan and explain the importance of the role of the counseling teacher in overcoming problems that are often experienced by students. This research is a qualitative descriptive research and seen by place is a field research. The subjects of this study were 292 students of SMPN 22 Medan. While the object of this research is the analysis of guidance and counseling problems that occur in students and the importance of the role of the counseling teacher in the implementation of religious guidance and counseling for students at the Junior High School level at SMP Negeri 22 Medan. Data collection methods consist of: interviews, observation and documentation. The results of this study: (1) The problems that often occur are that most students experience tardiness, long hair, clothing that is not according to the rules, carrying cell phones, fighting, smoking in the school environment, unplugging, dating and being absent more than 3 times. (2) The importance of guidance and counseling and the role of the counseling guidance teacher is urgently needed. BK teachers must also establish communication or collaborate with other teachers so that the educational process will run smoothly and make it easier to carry out the learning process. Therefore, as functional educators, counseling teachers are required to carry out various main tasks in a professional manner.